THE VIOLATION OF THE PRINCIPLES OF THE LAW RESERVATION AND THE REASONABILITY OF TAX ISSUES ON RULING LAW Nº 27260 ABOUT SINCERE FISCAL REGIME AND ITS PRETENDED UNCONSTITUTIONAL DECLARATION (Perspectivas de las Ciencias Económicas y Jurídicas, 2020)
The aim of this paper is to analyze, from a constitutional law perspective, and, more precisely, according to the legality, reasonability and reservation of tax law principles, the system of exclusion of subjects from the Sincere Fiscal Regime established by law nº 27260 and its ruling by decree nº 1206/2016.In addition, we will think about the unconstitutionality declaration of the rules when the use of the ruling power by the Executive Power that is exhibited on the side of what the Constitution allows. It also verifies how it breaks the constitutional limits that are established for tax issues. This, according to the “Sola” case of the 23th November 2017.
Keywords: Tax law; unconstitutionality; reasonability; legality